USE OF SIM (STRATEGIC INTERVENTION MATERIAL) AS STRATEGY AND THE ACADEMIC ACHIEVEMENT OF GRADE 7 STUDENTS ON SELECTED TOPIC IN EARTH SCIENCE - Villonez, Glen L (PUPIL: International Journal of Teaching, Education and Learning, 2018)
This research endeavor aimed to find out whether the use of SIM (Strategic Intervention Material) would improve the academic achievement of grade seven students on selected topic in earth science. The study made use of quasi experimental design which is non- equivalent control group pretest and posttest design. About 120 participants were used as subjects of the study. Mean and t- tests were used as tools in the analysis of data. The result of the study revealed that there was a significant difference in the pretest and posttest mean scores of the experimental and control group in the topic eclipse. The experimental group achieved a better mean gain score than the control group. This points out that the use of strategic intervention material (SIM) in the experimental group significantly improved the performance of the students. It can be concluded that the performance of students in the experimental group was greatly enhanced after SIM was employed in teaching the lesson. Therefore, the employment of SIM was better and effective than the use of traditional method in teaching some topic in science. Furthermore, it was recommended that SIM be adopted as instructional material or strategy in teaching science lessons as well as other subjects.